2003
DOI: 10.1046/j.1471-4159.2003.01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin AT4 ligands are potent, competitive inhibitors of insulin regulated aminopeptidase (IRAP)

Abstract: Angiotensin IV (Ang IV) exerts profound effects on memory and learning, a phenomenon ascribed to its binding to a specific AT 4 receptor. However the AT 4 receptor has recently been identified as the insulin-regulated aminopeptidase (IRAP). In this study, we demonstrate that AT 4 receptor ligands, including Ang IV, branes with high affinity, which was up to 200-fold greater than in the catalytic assay; this difference was not consistent among the peptides, and could not be ascribed to ligand degradation. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
181
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 158 publications
(187 citation statements)
references
References 24 publications
(60 reference statements)
3
181
1
2
Order By: Relevance
“…20,34) Both Ang IV and LVV-H7 display competitive kinetics indicating that AT 4 ligands mediate their effects by binding to the catalytic site of IRAP. 27) Using the same system we also have demonstrated that although the peptides Ang IV and LVV-H7 bind to the catalytic stie they are not cleaved by IRAP. 27) Although IRAP was cloned nearly a decade ago, AT 4 ligands are the first high affinity inhibitors of the enzyme to be identified.…”
Section: At 4 Ligands (Ang IV and Lvv-h7) Are In-hibitors Of Irapmentioning
confidence: 73%
See 2 more Smart Citations
“…20,34) Both Ang IV and LVV-H7 display competitive kinetics indicating that AT 4 ligands mediate their effects by binding to the catalytic site of IRAP. 27) Using the same system we also have demonstrated that although the peptides Ang IV and LVV-H7 bind to the catalytic stie they are not cleaved by IRAP. 27) Although IRAP was cloned nearly a decade ago, AT 4 ligands are the first high affinity inhibitors of the enzyme to be identified.…”
Section: At 4 Ligands (Ang IV and Lvv-h7) Are In-hibitors Of Irapmentioning
confidence: 73%
“…27) Using the same system we also have demonstrated that although the peptides Ang IV and LVV-H7 bind to the catalytic stie they are not cleaved by IRAP. 27) Although IRAP was cloned nearly a decade ago, AT 4 ligands are the first high affinity inhibitors of the enzyme to be identified. Development of stable, second generation inhibitors of IRAP based on the AT 4 ligands may provide the opportunity for the development of therapeutics for memory loss.…”
Section: At 4 Ligands (Ang IV and Lvv-h7) Are In-hibitors Of Irapmentioning
confidence: 73%
See 1 more Smart Citation
“…In this view, the multiple physiological actions of AngIV-related molecules are due to their ability to competitively inhibit IRAP, thus potentiating the actions of endogenous peptides that would normally be degraded by IRAP (Lew et al, 2003). However, there are several conceptual problems with this idea.…”
mentioning
confidence: 99%
“…angiotensin AT4 ligand (Ang IV) and insulin-regulated aminopeptidase. 16 The regional distribution of angiotensin receptor subtypes in the central nervous subtypes is shown in Table 1.…”
Section: Distribution Of Angiotensin Receptors In the Brainmentioning
confidence: 99%